2022
DOI: 10.1186/s12989-022-00457-y
|View full text |Cite
|
Sign up to set email alerts
|

Nano-titanium dioxide inhalation exposure during gestation drives redox dysregulation and vascular dysfunction across generations

Abstract: Background Pregnancy is associated with many rapid biological adaptations that support healthy development of the growing fetus. One of which is critical to fetal health and development is the coordination between maternal liver derived substrates and vascular delivery. This crucial adaptation can be potentially derailed by inhalation of toxicants. Engineered nanomaterials (ENM) are commonly used in household and industrial products as well as in medicinal applications. As such, the potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 79 publications
(95 reference statements)
0
19
1
Order By: Relevance
“…Females are smaller at GD 20 ( Griffith et al, 2022 ) ( Figure 2A ) and this same pattern of diminished growth persists up to 8-week (data not published). Additionally, adult females (∼10–11 weeks of age) exposed to nano-TiO 2 in utero will also have smaller pups at GD 20 ( Bowdridge et al, 2022 ) and have decreased plasma estrogen levels, which could be due to the decreased JZ area and mass seen in this study. In studies of mouse maternal nano-TiO 2 inhalation exposure during gestation we found that fetal hearts had decreased cardiac output and increased LV mass ( Kunovac et al, 2019 ).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Females are smaller at GD 20 ( Griffith et al, 2022 ) ( Figure 2A ) and this same pattern of diminished growth persists up to 8-week (data not published). Additionally, adult females (∼10–11 weeks of age) exposed to nano-TiO 2 in utero will also have smaller pups at GD 20 ( Bowdridge et al, 2022 ) and have decreased plasma estrogen levels, which could be due to the decreased JZ area and mass seen in this study. In studies of mouse maternal nano-TiO 2 inhalation exposure during gestation we found that fetal hearts had decreased cardiac output and increased LV mass ( Kunovac et al, 2019 ).…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, the placentas from nano-TiO 2 exposed dams have increased reactive oxygen species production rate (Bowdridge et al, 2022). Increased reactive oxygen species, like H 2 O 2 , has been shown to increase TXB 2 , the stable TXA 2 metabolite, production in hypertensive rat mesenteric arterioles (Gao and Lee, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations